Performance and Nutritional Attributes of Different Species of Oyster Mushroom (Pleurotus spp.) Cultivated under Different Growth Substrates - Ghimire, Ashish; Shrestha, Sundar Man; Thapa, Gopal (Journal of Agriculture and Resource Management, 2024)
Oyster mushroom (Pleurotus spp.) is cultivated on a wide range of substrates. However, the selection of appropriate species and substrate for its cultivation is crucial. This study, conducted in the two-factorial complete randomized design, was aimed at enhancing the performance of oyster mushrooms cultivated between November and March under sub-tropical conditions of Chitwan, Nepal through the selection of species and substrates. Three easily available substrates (paddy straw, water hyacinth, and corn cob) were used to cultivate three different species of oyster mushrooms (P. ostreatus, P. florida, and P. sajor-caju), and several parameters related to mycelial growth and yield were recorded. Water hyacinth was used along with paddy straw in the ratio 3:1 whereas paddy straw and corn cobs were used alone as separate treatments. The least number of days to spawn run completion was obtained from P. ostreatus grown on paddy straw (18 days) which was however statistically similar to several other combinations. The interaction between substrates and species of oyster mushroom showed no significant effect on the days to first harvest. In addition to early spawn run, the maximum Biological Efficiency (118.15%) and Benefit-Cost ratio (2.51) were also obtained from P. ostreatus on paddy straw. Besides, the combination of other species and substrates were also found superior based on nutritional attributes such as fiber, protein, and carbohydrate content. Cultivation of P. ostreatus on paddy straw can be considered optimal for the given conditions considering several growth, yield, and cost efficiency parameters however, some other locally available substrates such as water hyacinth and corn cobs can also be explored considering nutritional value and seasonal unavailability of paddy straw.